2014
DOI: 10.1007/978-3-319-08855-6_29
|View full text |Cite
|
Sign up to set email alerts
|

On Combining Regression Analysis and Constraint Programming

Abstract: Abstract. Uncertain data due to imprecise measurements is commonly specified as bounded interval parameters in a constraint problem. For tractability reasons, existing approaches assume independence of the parameters. This assumption is safe, but can lead to large solution spaces, and a loss of the problem structure. In this paper we propose to combine the strengths of two frameworks to tackle parameter dependency effectively, namely constraint programming and regression analysis. Our methodology is an iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After enlarging the interval bounds of the input data we were able to find a solution with a 50 % split of traffic, but none with 40 − 60 or other combinations. This experimental study showed the strong impact of taking into account dependency constraints with simulations [13].…”
Section: Traffic Conservation Constraintsmentioning
confidence: 83%
“…After enlarging the interval bounds of the input data we were able to find a solution with a 50 % split of traffic, but none with 40 − 60 or other combinations. This experimental study showed the strong impact of taking into account dependency constraints with simulations [13].…”
Section: Traffic Conservation Constraintsmentioning
confidence: 83%
“…The solution sets produced can be very large. This led to some research to extract the relationship between uncertain data that satisfy dependency constraints and possible solutions by applying regression analysis techniques [11]. The fuzzy and mixed CSP [9] coined the concept of uncontrollable variables, that can take a set of values but their domain is not meant to be pruned during problem solving (unlike decision variables).…”
Section: Related Workmentioning
confidence: 99%